2023
DOI: 10.3332/ecancer.2023.1499
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of taurine, piracetam and vinpocetine on etoposideinduced inflammation and brain injury in the serum of female albino rats

Abstract: Etoposide (ETP) is one of the leading antitumour agents in cancer chemotherapy. Many studies have reported on ETP-induced peripheral neuropathy; however, few reports have focused on its brain toxicity. The current research investigates the protective potential of taurine, piracetam and vinpocetine on serum biomarkers associated with inflammation and brain injury induced by ETP in a rodent model. A total of 30 female albino rats were equally divided into five groups; the 1 st and 2 nd groups were the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Alkaloids, a class of nitrogen compounds with heterocyclic structures and significant biological activity, warrant attention 62 . Vinpocetine, in particular, displays anti-inflammatory and antioxidant effects, offering the potential for reducing the toxicity of certain chemotherapy drugs, such as cisplatin-induced acute kidney injury 63 and etoposide-induced brain injury 64 . Moreover, vinpocetine has shown promise in mitigating SARS-CoV-2-induced hyper-inflammatory and oxidative stress 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids, a class of nitrogen compounds with heterocyclic structures and significant biological activity, warrant attention 62 . Vinpocetine, in particular, displays anti-inflammatory and antioxidant effects, offering the potential for reducing the toxicity of certain chemotherapy drugs, such as cisplatin-induced acute kidney injury 63 and etoposide-induced brain injury 64 . Moreover, vinpocetine has shown promise in mitigating SARS-CoV-2-induced hyper-inflammatory and oxidative stress 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, piracetam was used as a positive control due to its known protective effects. Piracetam enhances cholinergic functions and reduces neuronal inflammation, apoptosis and oxidative stress, thus highlighting its beneficial effects as a therapeutic agent ( 45 , 46 ). Previous studies have demonstrated that administration of piracetam at doses of 250 or 500 mg/kg via the intraperitoneal (i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…After that, a freshly eluted pertechnetate solution (~ 350 MBq) from a Moly generator was added to this mixture and subsequently incubated at room temperature for 25 min. In order to determine the optimal labeling conditions, different combinations of factors affecting the labeling yield were studied using varying amounts of fonturacetam hydrazide (5-50 µg), Stannous chloride dihydrate (25-250 µg) at different pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) for different reaction times (5-40 min).…”
Section: Labeling Of Fonturacetam Hydrazidementioning
confidence: 99%
“…They are mainly used as nootropic drugs to treat cognitive deficits. Although the exact mechanism of action of racetams is not fully comprehended [8], they are thought to produce their effect by primarily modulating the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors [9,10]; the predominant excitatory neurotransmitter receptors mediating synaptic transmission in the brain. The AMPA receptors dysfunction is thought to underlie certain neuronal disorders, including depression, schizophrenia, epilepsy, and Alzheimer's disease [11][12][13], and their synaptic trafficking is believed to underlie neuronal plasticity, including learning and memory [14,15].…”
Section: Introductionmentioning
confidence: 99%